Large Ring Test for Evaluation of Restrained Shrinkage Cracking: Calibration and Experimental Trial - Zhongyu Xu; Lucija Hanžič; Harry Asche; Jurij Karlovšek (Advances in Civil Engineering)
The durability of shotcrete tunnel linings is significantly affected by restrained shrinkage cracking. Given the unique characteristics of shotcrete applied in tunnel linings, especially when dealing with accelerated shotcrete containing reinforcement fibres, it is necessary to upscale the ring test commonly used. This paper presents a comprehensive experiment using large ring tests with cast concrete to investigate the impact of upscaling ring test geometry. The two ring specimens demonstrated comparable cracking age (22 days) and strain measured in the steel ring, suggesting that consistent results can be obtained through the proposed instrumentation, calibration, and correction methods. Moreover, the estimated induced tensile stresses of the concrete rings (2.8 and 2.7 MPa) are slightly lower than the predicted tensile strength (3.3 MPa) at the age of cracking, which indicates that some driving forces contributing to restrained shrinkage cracking were not indicated in the strain gauge readings. Furthermore, the study identified multi-crack formation and additional potential causes for crack initiation, which include self-restraint due to the moisture gradient in the vertical direction, deflection of the concrete ring caused by its self-weight, and friction on the contact surface of the support. Therefore, optimising the geometry of the ring specimens and the apparatus is imperative to minimise additional driving forces and unmeasurable restraints for crack initiation, especially when employing the stress rate method to assess cracking potential.